A retrospective analysis based on multiple machine learning models to predict lymph node metastasis in early gastric cancer - Yang, Tao; Martinez-Useros, Javier; Liu, JingWen; Alarcón, Isaias; Li, Chao; Li, WeiYao; Xiao, Yuanxun; Ji, Xiang; Zhao, YanDong; Wang, Lei; Morales-Conde, Salvador; Yang, Zuli (Frontiers in Oncology, 2022)
Background: Endoscopic submucosal dissection has become the primary option of treatment for early gastric cancer. However, lymph node metastasis may lead to poor prognosis. We analyzed factors related to lymph node metastasis in EGC patients and we developed a construction prediction model with machine learning using data from a retrospective series. Methods: Two independent cohorts’ series were evaluated including 305 patients with EGC from China as cohort I and 35 patients from Spain as cohort II. Five classifiers obtained from machine learning were selected to establish a robust prediction model for lymph node metastasis in EGC. Results: The clinical variables such as invasion depth, histologic type, ulceration, tumor location, tumor size, Lauren classification, and age were selected to establish the five prediction models. Linear Support Vector Classifier (Linear SVC), Logistic regression model, Extreme Gradient Boosting model (XGBoost), Light gradient boosting machine model (LightGBM), and Gaussian Process Classification model. Interestingly, all prediction models of cohort I showed an accuracy between 70% and 81%. Furthermore, the prediction models of cohort II exhibited an accuracy between 48% and 82%. The Areas Under Curve (AUC) of the five models between cohort I and cohort II were between 0.736 and 0.830. Conclusions: Our results support that the machine learning method could be used to predict lymph node metastasis in early gastric cancer and perhaps provide another evaluation method to choose the suited treatment for patients.